Eksplorasi Praktik Manajemen Keuangan pada Usaha Mikro Toko Sembako di Desa Samban, Kabupaten Semarang - Ernawati Laia; Renny Aprilliyani (Mahesa Research Center, 2026)
This study aims to explore financial management practices in micro grocery store businesses in Samban Village, Semarang Regency. The problem focuses on how entrepreneurs manage financial records, cash flow, business capital, and financial decision-making. This research employs a qualitative exploratory approach involving 6 grocery store owners selected through purposive sampling. Data were collected through in-depth interviews, observations, and documentation, and analysed using an interactive analysis model. The results indicate that financial management practices remain simple and informal, characterised by the use of basic cash books, reliance on daily sales revenue for capital turnover, and the absence of clear separation between business and household finances. However, entrepreneurs demonstrate practical strategies to maintain cash flow and sustain their businesses. This study contributes by providing empirical insights into real financial management practices at the micro-business level and serves as a basis for developing financial literacy and assistance programs for micro-entrepreneurs.